Death of the Slaveboy (Part Two) - Bergmar, Magnus (Sweden, 1999)
Second part of a film about the life and death of Iqbal Masih, murdered human rights activist and former bonded child slave in the Pakistani carpet industry. This segment examines the tragic death of Iqbal Masih and investigates the charges that his death was part of a conspiracy against him by Pakistan's carpet "mafia." Through the interviews featured, this part also dwells deeper into the issue of child labor and slavery in Pakistan.
Soros Documentary Fund
Soros Documentary Fund
Keywords: Documentary films